An Incidentally Detected Right Ventricular Pseudoaneurysm - Vamsi C. Gaddipati; Angel I. Martin; Mauricio O. Valenzuela; Asef Mahmud; Aarti A. Patel (Case Reports in Cardiology)
Ventricular pseudoaneurysm is an uncommon, potentially fatal complication that has been associated with myocardial infarction, cardiac surgery, chest trauma, and infectious processes. Diagnosis can be challenging, as cases are rare and slowly progressing and typically lack identifiable features on clinical presentation. As a result, advanced imaging techniques have become the hallmark of identification. Ahead, we describe a patient who presents with acute decompensated heart failure and was incidentally discovered to have a large right ventricular pseudoaneurysm that developed following previous traumatic anterior rib fracture.